Análise da dinâmica da transição do regime de fogo na Amazônia brasileira - TAVARES, Paulo Amador (Universidade Federal do Pará, 2025)
The Amazon biome has undergone significant changes in land use and land cover, and it is also being affected by global climate change. Consequently, the fire occurrence has become more frequent in the Amazon. Therefore, it is important to understand how the fire regime in this region occurs and its interactions with land use and climate. For these reasons, this study analyses the fire transition in the Brazilian Amazon. In Chapter 1, we investigated the temporal fire transition in the Brazilian Amazon, considering changes in land use and forest cover. We collected annual data on fire occurrence, forest cover, deforestation rates, and soybean cultivation areas. Generalized linear mixed models and linear models were used to analyse the data and identify the key factors influencing this transition. We found that there is a fire transition process in the forest, and a quadratic model provided a better prediction of fire occurrence behaviour. Furthermore, the peak of fire occurrence is shifting towards more forested landscapes over time. Deforestation rates and the expansion of cultivation areas were found to be related to this transition, with deforestation having a greater impact on fire occurrence and cultivation expansion being more relevant in predicting the transition to more forested areas. In Chapter 2, we investigated the fire transition in forest landscapes of the Brazilian Amazon, aiming to understand how this transition occurs and which variables best explain the process. We used Latent Trajectory Analysis (LTA) and generalized linear mixed models to identify latent trajectories representing different patterns of land use over time. Two main latent trajectories were identified: the "Consolidated" trajectory, characterized by a longer history of deforestation, and the "Transition" trajectory, characterized by a more recent land occupation pattern. Forest cover and deforestation were the main predictors of forest fires in both trajectories, followed by water deficit. Mechanized agriculture did not show significant influence on either trajectory. An increase in burned forest areas was observed from 2015 onwards in both trajectories. Overall, these findings highlight the importance of the fire transition in the Brazilian Amazon and its relationship with land use changes and forest cover. They underscore the need to develop public policies that strengthen forest cover through initiatives like forest restoration and reduce deforestation in the Amazon region to ensure biodiversity conservation and carbon stocks.